2021
DOI: 10.1007/s12274-021-3561-2
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-doped graphene anchoring of ultrafine Au25 nanoclusters for electrocatalysis

Abstract: The anchoring effect origin from sulfur-doped graphene enables a significantly enhanced stability of ultrafine Au nanoclusters during electrocatalytic nitrogen reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The application of Au NCs as electrocatalysts to explore the transformation of dinitrogen (N 2 ) to ammonia (NH 3 ) through the electrocatalytic process is another interesting research topic. However, so far very few reports have demonstrated the NRR using mono- or bimetallic Au NCs. Nevertheless, in most cases, the yields of NH 3 and FEs were much less due to the competing HER. Therefore, the key strategies to improve the yield of NH 3 would be constraining the competing HER and introducing more active sites by modulating the electronic structure of active sites.…”
Section: Discussionmentioning
confidence: 99%
“…The application of Au NCs as electrocatalysts to explore the transformation of dinitrogen (N 2 ) to ammonia (NH 3 ) through the electrocatalytic process is another interesting research topic. However, so far very few reports have demonstrated the NRR using mono- or bimetallic Au NCs. Nevertheless, in most cases, the yields of NH 3 and FEs were much less due to the competing HER. Therefore, the key strategies to improve the yield of NH 3 would be constraining the competing HER and introducing more active sites by modulating the electronic structure of active sites.…”
Section: Discussionmentioning
confidence: 99%
“…For example, on account of the strong bond between Au and S atoms, Li et al used S-doped graphene as a support to stabilize the Au 25 (PET) 18 cluster. 104 Au 25 @S-G exhibits remarkable NRR activity. Yang et al reported a core-shell NPF@ZIF-8 for the NRR with a high FE of 44% and excellent NH 3 yield of (28.7 AE 0.9) mg h À1 cm À2 .…”
Section: Catalytic Performance Of Metal Nanoclusters For the Nrrmentioning
confidence: 99%
“…In a cluster-sensitized PEC, either the photoinduced electron or the hole generated at the cluster would be transferred from the cluster to the semiconductor, collected by the current collector and transferred to the counter electrode through an external circuit . Because it is the ligand that is in contact with the semiconductor, the electronic properties of the ligand would affect the transport of the carriers between the cluster and the semiconductor, thus directly governing the performance of the photoelectrode. , Although the ligand effect of metal NCs and NPs has been extensively studied in catalytic applications from the aspects of steric hindrance, coordination mode, solubility, and so on, studies focusing on the electronic properties of the ligand are rare. …”
Section: Introductionmentioning
confidence: 99%